Willingness to receive COVID-19 vaccine and associated factors among teachers in Dambi Dollo, Ethiopia: a cross-sectional study - Desalegn Shiferaw; Chara Melaku; Lemessa Assefa; Tadele Kinati (BMC Public Health)
Abstract Background Teachers play important roles in influencing vaccine uptake decisions and should serve as examples for their students by willingly getting vaccinated. Given the low vaccination rates in this area, it is crucial to explore teachers’ willingness to get vaccinated and emphasize their role in promoting vaccine acceptance. Objective The main objective of this study was to assess the willingness of teachers to receive the COVID-19 vaccine and its associated factors in Dambi Dollo town. Methods A school-based cross-sectional study was conducted from February 1 to March 30, 2022. Data were collected using a self-administered questionnaire and analysed with SPSS version 23.0. The dependent variable was willingness to receive the COVID-19 vaccine. Variables that showed an association with the dependent variable in the bivariable analyses at a p-value of 0.25 were entered into a multiple stepwise logistic regression model. A p- value of 0.05 was considered statistically significant in this study’s multivariable analysis to determine the presence of significant association between the dependent and the independent variables. Adjusted Odds ratios, along with the corresponding 95% confidence intervals were used to interpret the findings. Results A total of 247 teachers participated in this study. About 92% of the teachers in Dambi Dollo town have heard COVID-19 vaccine and 67.2% of them knew that the vaccine can prevent the COVID-19 disease. On the other hand, 51% (95%CI: 44.8, 57.2) of the respondents had good knowledge about the COVID-19 vaccine. From the total 247 participants, 68.4% (95%CI: 62.5, 74.3) were willing to receive the vaccine immediately while the remaining were either not willing or not ready at the time of data collection. Those participants having good knowledge of the vaccine were about six times more willing to get vaccinated (AOR = 5.85, 95%CI: 2.74, 12.47) in comparison with those having poor knowledge. Conclusion In conclusion, the level of willingness to receive the COVID-19 vaccine among school teachers in Dambi Dollo town was 68.4. Followers of Protestant religion and Muslims were less willing compared with Orthodox Christians while the participants with good knowledge were more willing to be vaccinated.